2022
DOI: 10.3390/biom12081051
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Stem-Like Cells (GSCs) with Mesenchymal Signature: Lipid Profiles of Mobile Lipids Obtained with MRS before and after Radio/Chemical Treatments

Abstract: Glioblastoma is the most common and lethal primary malignant brain tumor in adults. Glioblastoma stem cells (GSCs) promote and are responsible for glioblastoma intratumoral heterogeneity and therapy resistance, due to their two main features: self-renewal and differentiation. Lipids have important biological and physiological functions that are critical for understanding the regulation and control of stem cell fate; lipid metabolism and related unsaturation levels play a possible role as the target of therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Grande et al applied MRS in glioblastoma stem-like cells and detected multiple metabolites in vitro, indicating an important role of mitochondrial fatty oxidation in energy supplements in glioblastoma stem-like cells [30]. They also discovered specific metabolic signatures of glioblastoma stem-like cells after stressful treatments via MRS detection [31]. All the studies suggest more advanced utilization of MRS in metabolic investigations and clinical practice, and further investigations could be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Grande et al applied MRS in glioblastoma stem-like cells and detected multiple metabolites in vitro, indicating an important role of mitochondrial fatty oxidation in energy supplements in glioblastoma stem-like cells [30]. They also discovered specific metabolic signatures of glioblastoma stem-like cells after stressful treatments via MRS detection [31]. All the studies suggest more advanced utilization of MRS in metabolic investigations and clinical practice, and further investigations could be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…1 H MRS provides irreplaceable information for the diagnosis and therapeutic monitoring of tumors, particularly gliomas [21][22][23]. Studies have shown that the metabolite ratio has a specific value in differentiating treatment-related changes (radiation necrosis and tumor pseudoprogression) from tumor recurrence in gliomas [24][25][26]. Total choline (tCho) is considered a biomarker reflecting the state of cell membrane turnover and has been widely used to identify tumor areas with excessive cell proliferation and for the therapeutic monitoring of gliomas [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the relationship between metabolite alterations and oncogenic expression [31]. In in vitro MRS research, the scientific detection of metabolites could be analyzed by combining certain gene expression and cell biological behaviors [23,25], which could provide excellent feedback on cellular states in tumor progression. These in vitro research achievements may be transformed into in Vivo MRS studies to sufficiently comprehend new clinical MRS discoveries [32].…”
Section: Introductionmentioning
confidence: 99%